Using Taylor Rule to Explain Effects of Institutional Changes in Central Banks - Aleksandra Maslowska (Aboa Centre for Economics (ACE), 2009)
In this paper we trace changes in monetary policy caused by institutional amendments in legal acts of central banks. We estimate coefficients of the Taylor Rule for central banks of Sweden, United Kingdom, Switzerland and EU15 to shed some light on monetary policy ex ante and ex post significant improvements in central bank independence. Results presented suggest differences in accommodating monetary policy in countries and support the idea that initial level of CBI matters for reactions to variability both of inflation and output gap. A preindependence period characterizes with strong inflation targeting features, whereas a post-independence time resembles more discretionary type of monetary policy. As a spin-off from our original idea, we find that changing properties of inflation in the last decade make econometric analysis more difficult
Keywords: E02; E52; 330; Taylor rule; central bank independence; interest rate rules